Bank customers' reception towards internet banking - Adnan, Khairul Anuar; Ahmad, Nor Hayati; Rozali, Mohammad Badri; Mohamed Zabri, Shafie (2005)
The objective of this study is to investigate the factors influencing the reception of bank customer towards internet banking in Malaysia.The literature on internet banking in Malaysia covers widely on the benefits of internet banking.However we find that the usage of internet banking among Malaysian bank customers is still low compared to more develop countries.Our study find that security concern, lack of awareness and reluctant to change or to adopt new technology as the prime reasons for slow reception of internet banking in Malaysia.Bank management could instill greater confidence by providing adequate education on security concern.A lesson to be learnt from the Malaysia experience is that public education and information dissemination should be in line with technological innovation and advances in financial sector.